„Kiedy gwiazdy się na niebie złocą…” Metaforyka jubilerska w rzymskich opisach nieba - Piętka, Radosław (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2016)
Metaphors and comparisons are typical features of the ancient texts describing celestial bodies, and they can be treated as a part of a broader cultural practice of seeking analogies between earth and sky phenomena, inspired by the microcosm/macrocosm theory. To explain such a practice we can refer to the modern theory of imagination as well, according to which appreciation of nature is based, among others, on the so-called “projective imagination”, transferring mentally the images from the terrestrial reality to the sky. One of the obvious instances of such an analogical thinking is “katasterismos”, mythic narration about the item placed in the heavens as a star or constellation. It appears that among the objects on the sky described as a result of “catasterism” we can find some specimens of jeweller’s craftsmanship (e.g. Ariadne’s Crown as Corona Borealis). This is, however, a specific situation; astronomical descriptions usually emphasize the brightness and perfection of the sky phenomena using above-mentioned poetic devices associated with jewellery. Most popular among them is the metaphoric epithet of “gold”, linked commonly with stars and the sun, but besides this, in the works of Roman authors can be detected more original imagery (e.g. the cosmos as a necklace). It is argued in the paper that this kind of astronomical descriptions can be interpreted against the backdrop of the history of the “visual metaphors of value”, as they were defined by Ernst Gombrich.